Clinical Utility and Analytical Challenges in Measurement of Cerebrospinal Fluid Amyloid-β(1–42) and τ Proteins as Alzheimer Disease Biomarkers - Kang, Ju-Hee (2013)
BACKGROUND: Over the past 2 decades, clinical studies have provided evidence that cerebrospinal fluid (CSF) amyloid β(1–42) (Aβ(1–42)), total τ(t-τ), and τ phosphorylated at Thr181 (p-τ(181)) are reliable biochemical markers of Alzheimer disease (AD) neuropathology. CONTENT: In this review, we summarize the clinical performance and describe the major challenges for the analytical performance of the most widely used immunoassay platforms [based on ELISA or microbead-based multianalyte profiling (xMAP) technology] for the measurement of CSF AD biomarkers (Aβ(1–42), t-τ, and p-τ(181)). With foundational immunoassay data providing the diagnostic and prognostic values of CSF AD biomarkers, the newly revised criteria for the diagnosis of AD include CSF AD biomarkers for use in research settings. In addition, it has been suggested that the selection of AD patients at the predementia stage by use of CSF AD biomarkers can improve the statistical power of clinical trial design. Owing to the lack of a replenishable and commutable human CSF-based standardized reference material (SRM) and significant differences across different immunoassay platforms, the diagnostic–prognostic cutpoints of CSF AD biomarker concentrations are not universal at this time. These challenges can be effectively met in the future, however, through collaborative ongoing standardization efforts to minimize the sources of analytical variability and to develop reference methods and SRMs. SUMMARY: Measurements of CSF Aβ(1–42), t-τ, and p-τ(181) with analytically qualified immunoassays reliably reflect the neuropathologic hallmarks of AD in patients at the early predementia stage of the disease and even in presymptomatic patients. Thus these CSF biomarker tests are useful for early diagnosis of AD, prediction of disease progression, and efficient design of drug intervention clinical trials.